Factors affecting turnover intention in Tirai Selera Sdn Bhd / Nurfatihah Sazali and Siti Aishah Bakri - Sazali, Nurfatihah; Bakri, Siti Aishah (Faculty of Business and Management, 2016)
Purpose - To examine how job satisfaction, salary (compensation), co-worker relationship, workload, training and work environment influence the turnover intention in Tirai Selera Sdn Bhd.